Bacterial, protozoal and viral abortions in sheep and goats in South America: a review - Dorsch, Matías A. (2021)
Bacterial, protozoal and viral diseases are major causes of abortion in sheep and goats. These agents cause significant economic losses, and many are considered of concern for public health (zoonotic pathogens) and/or the international trade of livestock, such as those causing diseases notifiable to the World Organization of Animal Health (OIE). In South America, information about their occurrence, prevalence and economic impact is scarce. We review the available literature on bacterial, protozoal and viral abortifacients identified through laboratory testing in sheep and goats in South America and discuss whether the diagnostic investigations are conclusive in demonstrating abortion causality. We also compile information on diagnostic methods recommended by the OIE for the laboratory diagnosis of these abortifacients and on salient fetoplacental lesions induced by them. Campylobacteriosis (Campylobacter fetus subsp. fetus), listeriosis (Listeria ivanovii), chlamydiosis (Chlamydia abortus), toxoplasmosis, neosporosis and sarcocystiosis have been confirmed as small ruminant abortifacients in this region. Brucella ovis, Brucella melitensis, Campylobacter jejuni, Chlamydia pecorum, Coxiella burnetii, Leptospira spp., Bacillus licheniformis and bluetongue virus, are probable causes of abortion in the region since they have been detected in aborted fetuses and/or associated with abortions through seroepidemiologic studies. Listeria monocytogenes, Histophilus ovis, Actinobacillus seminis, Trueperella pyogenes, Yersinia spp., Trypanosoma vivax, caprine herpesvirus 1 and pestiviruses also infect small ruminants in the region and could thus be considered possible causes of abortion, although they have not been associated with abortion in South America (i.e., not detected in aborted fetuses nor associated with abortion through seroepidemiologic studies). Other agents such as Flexispira rappini, Francisella tularensis, Anaplasma phagocytophilum, Rift Valley fever virus, Wesselbron disease virus and bunyaviruses, known to be abortifacients for sheep and goats in other regions of the world, have not been documented in South America. While some of these agents could be exotic in this subcontinent, others may have been undiagnosed considering the limitations of active animal disease surveillance systems, which hamper the eventual detection of emerging, re-emerging, and communicable diseases in South America.